2009
DOI: 10.1111/j.1463-1318.2008.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma magnesium should be monitored perioperatively in patients undergoing colorectal resection

Abstract: Bowel preparation with Picolax does not appear to cause significant electrolyte disturbance, except in elevating plasma magnesium. Postcolorectal resection plasma magnesium dropped significantly suggesting perioperative monitoring and replacement should be routine following colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, this result is controversial among studies. Whereas some studies found no significant changes in electrolytes [31], other studies found that the reduction in serum electrolyte levels was significant only in elderly patients [32]. Therefore, when SPMC preparations are utilized, practitioners should instruct their patients to take sufficient fluids to prevent dehydration and carefully monitor use among older patients.…”
Section: Discussionmentioning
confidence: 96%
“…However, this result is controversial among studies. Whereas some studies found no significant changes in electrolytes [31], other studies found that the reduction in serum electrolyte levels was significant only in elderly patients [32]. Therefore, when SPMC preparations are utilized, practitioners should instruct their patients to take sufficient fluids to prevent dehydration and carefully monitor use among older patients.…”
Section: Discussionmentioning
confidence: 96%
“…Many of those are well known and measured routinely. [3,[12][13][14][15][16][17][18][19] For example, postoperative serum potassium or hematocrit levels were assessed routinely for replacement or transfusion. Other parameters like serum albumin or total calcium level reflect the magnitude of fluid and electrolyte imbalances caused by the operative procedures and its anesthesiologic resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have not examined the magnitude of alteration in postoperative Mg level in gynecological abdominal surgeries or its impact on postoperative outcome in females only. [3,[12][13][14][15][16][17][18]20] Postoperative hypomagnesemia has been reported in other types of operation like major cancer series, cardiac, colorectal surgeries, thyroidectomies, and spinal fusion. [13][14][15][16][17][18]20,21] Recompense of lowered serum Mg perioperatively has some benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations